Views and perceptions of advanced life support practitioners on initiating, withholding and terminating resuscitation in out of hospital cardiac arrest in the emergency medical services of the Western Cape - Higgins, Sarah (Division of General Surgery, 2024)
Non-communicable disease as a cause of death is on the rise. Cardiovascular disease was the main non-communicable cause of death in South Africa and the Western Cape in 2018, comprising of 18.9% of all deaths in the country. (1) Cardiovascular disease remains the predominant cause of out-of-hospital cardiac arrest (OHCA). (2) The overall prognosis and neurological outcome associated with OHCA are rather poor and have remained unchanged for the past thirty years. There is a survival rate of approximately 10% following discharge from hospital. (3, 4) This is from the United Kingdom and the United States, which are both high-income countries (HIC). Overall survival following OHCA in low-to-middle-income countries (LMIC) has been reported to be poor, but studies are limited. (5, 6) South Africa is an LMIC with a limited healthcare budget and resources and is thus likely to have a lower survival rate than other HICs.